THE POLITICS OF WOMEN’S BODIES IN BEFORE SHE SLEEPS: A FEMINIST ANALYSIS OF REPRODUCTIVE EXPLOITATION, AUTONOMY AND TRAUMA - Anosha Khaliq; Faheem Arshad (International Premier Journal of Languages & Literature, 2026)
This research aims to examine the reproductive exploitation, limited autonomy, and the trauma in Shah’s Before She Sleeps (2018). It investigates these harsh realities from a feminist perspective, while drawing on Kate Millet’s work Sexual Politics. Through a dystopian narrative, it discloses a regime set in Green City that exploits, manipulates, and controls women’s bodies to serve the state’s reproductive needs. It critically examines the deep-rooted societal institutions that facilitate patriarchy to maintain its hegemony. While existing scholarship has explored resistance, rebellion, and gendered exploitation in this text extensively, limited attention has been given to Shah’s work within this critical framework of Kate Millet. This research addresses this gap by analyzing how the novel portrays the resistance against reproductive exploitation and the societal expectations imposed on women's bodies in a compelling critique of patriarchal structures of society. It also uncovers the trauma women face while going through these horrendous experiences. Using qualitative textual analysis, this research applies Millet’s idea of patriarchy as an institution that regulates gender and sexuality. It contributes to feminist dystopian studies by illustrating how literature can challenge the entrenched patriarchal norms by criticizing reproductive slavery and the social construction of gendered power.